The Taliban at war: 2001-2018 - Giustozzi, Antonio (Oxford University Press, 2019)
Introduction --The collapse of the Emirate and the early regrouping, 2002-4 --The apogeum of the Quetta Shura, 2005-9 --The emergence of alternative centres of power to Quetta --The crisis of the Quetta Shura 2009-13 --The Taliban's tactical adaptation --Organisational adaptation --The troubled comeback of the Quetta Shura 2014 --Conclusion.The impossible centralisation of an anti-centralist movement --Epilogue.